2012
DOI: 10.1091/mbc.e12-04-0260
|View full text |Cite
|
Sign up to set email alerts
|

Human Cdc14A regulates Wee1 stability by counteracting CDK-mediated phosphorylation

Abstract: Cdc14A phosphatase regulates Wee1 kinase through dephosphorylation of two Cdk phosphorylation sites in its regulatory domain, Ser-123 and -139, both involved in the degradation of Wee1 at the entry into mitosis. In this way, Cdc14A interferes with the negative feedback loop between Wee1 and Cdk1 to regulate the mitotic switch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
41
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 43 publications
8
41
1
9
Order By: Relevance
“…Previous studies have shown that for cells to activate CDK2, CDK2 protein has to bind to its regulatory subunit cyclin E or A, the Thr160 site has to be phosphorylated by CDK activator (CAK), and CDC25 has to dephosphorylate its Thr14 and Tyr15 sites 14, 15. Our data showed that the phosphorylation levels of CDK2 Thr160 and Thr14/Tyr15 were not affected by DOC-1R overexpression (Fig.…”
Section: Resultssupporting
confidence: 49%
“…Previous studies have shown that for cells to activate CDK2, CDK2 protein has to bind to its regulatory subunit cyclin E or A, the Thr160 site has to be phosphorylated by CDK activator (CAK), and CDC25 has to dephosphorylate its Thr14 and Tyr15 sites 14, 15. Our data showed that the phosphorylation levels of CDK2 Thr160 and Thr14/Tyr15 were not affected by DOC-1R overexpression (Fig.…”
Section: Resultssupporting
confidence: 49%
“…To determine whether hCDC14A localization changes upon perturbation of the F-actin cytoskeleton, we treated cells with blebbistatin, a myosin II inhibitor that inhibits F-actin formation. Blebbistatin treatment prompted all three tagged versions of hCDC14A to join F-actin remnants in relocalizing to peripheral regions of the cell ( We next monitored the distribution of endogenous hCDC14A with polyclonal antibodies that had been raised against the divergent C terminus of hCDC14A (26,27). These anti-hCDC14A antibodies costained the cell leading edge and the nearby actin filaments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While MCM5 and ORC1 associate with both cyclin E and cyclin A, only ORC1 inhibits cyclin/CDK2 activity. CDC14 dephosphorylates certain CDK substrates and may counteract CDK-mediated phosphorylation of centrosomal substrates (58, 59). RBM14 has no connection to CDK2; it suppresses the assembly of centriolar protein complexes that would lead to the formation of extra centrioles.…”
Section: Discussionmentioning
confidence: 99%